PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR INDUSTRI TEKSTIL DAN GARMEN TERDAFTAR GO PUBLIK DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Evrina, Evrina; Rozi, A.; Mariana, Repilia; Budianto, Achyat (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research was conducted to examine the effect of return on assets (ROA) and net profit margin (NPM) on share prices in textile and garment industry sub-sector companies that go public on the Indonesia Stock Exchange for the 2018–2022 period. The approach used in this research is an associative one. In this study, there were 10 companies as a population, with 2 companies used as a sample. The source of the data used in this study is the financial statements of the textile and garment industry sub-sector companies that went public on the Indonesia Stock Exchange for the 2018–2022 period. The data collection technique used in this study is the documentation technique. In this study, there were five types of data collection techniques: descriptive statistics, classical assumptions test, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this study prove that return on assets (ROA) and net profit margin (NPM) partially affect stock prices. And simultaneously, return on assets (ROA) and net profit margin (NPM) affect share prices in textile and garment industry sub-sector companies that go public on the Indonesia Stock Exchange for the 2018–2022 period.